Lactobacillus rhamnosus GG and Bifidobacterium longum Attenuate Lung Injury and Inflammatory Response in Experimental Sepsis - Khailova, Ludmila (Public Library of Science, 2014)
INTRODUCTION: Probiotic use to prevent nosocomial gastrointestinal and potentially respiratory tract infections in critical care has shown great promise in recent clinical trials of adult and pediatric patients. Despite well-documented benefits of probiotic use in intestinal disorders, the potential for probiotic treatment to reduce lung injury following infection and shock has not been well explored. OBJECTIVE: Evaluate if Lactobacillus rhamnosus GG (LGG) or Bifidobacterium longum (BL) treatment in a weanling mouse model of cecal ligation and puncture (CLP) peritonitis will protect against lung injury. METHODS: 3 week-old FVB/N mice were orally gavaged with 200 µl of either LGG, BL or sterile water (vehicle) immediately prior to CLP. Mice were euthanized at 24 h. Lung injury was evaluated via histology and lung neutrophil infiltration was evaluated by myeloperoxidase (MPO) staining. mRNA levels of IL-6, TNF-α, MyD88, TLR-4, TLR-2, NFΚB (p50/p105) and Cox-2 in the lung analyzed via real-time PCR. TNF-α and IL-6 in lung was analyzed via ELISA. RESULTS: LGG and BL treatment significantly improved lung injury following experimental infection and sepsis and lung neutrophil infiltration was significantly lower than in untreated septic mice. Lung mRNA and protein levels of IL-6 and TNF-α and gene expression of Cox-2 were also significantly reduced in mice receiving LGG or BL treatment. Gene expression of TLR-2, MyD88 and NFΚB (p50/p105) was significantly increased in septic mice compared to shams and decreased in the lung of mice receiving LGG or BL while TLR-4 levels remained unchanged. CONCLUSIONS: Treatment with LGG and BL can reduce lung injury following experimental infection and sepsis and is associated with reduced lung inflammatory cell infiltrate and decreased markers of lung inflammatory response. Probiotic therapy may be a promising intervention to improve clinical lung injury following systemic infection and sepsis.